IMPROVING THE ANALYSIS OF THE EFFICIENCY OF THE BANKING SECTOR USING MODERN STATISTICAL METHODS (Academicia Globe: Inderscience Research, 2022)
The article discusses methodological approaches to the formation of an assessment of the banking sector's efficiency, the issues of methodological support of statistical analysis of efficiency management.